Transcription and recombination factories: Common features? - Lucas, Joseph S (2010)
There is now substantial evidence that the eukaryotic nucleus consists of highly organized structures. Among such structures are transcription factories that consist of an ensemble of genes recruited by the RNA polymerase machinery. Here we suggest that antigen receptor variable regions are similarly organized. Specifically, we propose that the immunoglobulin heavy chain locus variable gene segments are anchored to the base of rosettes, wrapping around a cavity that contains the recombination machinery. We suggest that the folding of the chromatin fiber into rosettes underpins a critical mechanism by which antigen receptor diversity is generated.